ANALYSIS OF FACTORS RELATED TO FOOD SECURITY IN MALANG PROVINCE EAST JAVA - Ahmad Dedy Syathori; Yayuk Yuliati; Keppi Sukesih; Ismulhadi Ismulhadi (Agricultural Socio-Economics Journal, 2018)
Indonesia is one of the populated countries which still has high population growth. It will influence the food supply. The more the number of population, the demand for food will increase. Other food problems occur because of the limited resources available and the lack of infrastructure for farming activities. This study has the objective to analyze what factors are associated with food security in Malang. The method research approach used in this research is descriptive qualitative research approach. Sources of information or informants in this study are the agricultural extension field, the main actors, and public figures. Results of research on factors associated with food security in Malang is a factor of production, post-harvest, marketing, innovation, the participation of farmers, and behavioral changes. Activities to empower farmers program implemented should involve the participation of key actors and activities undertaken farmers’ empowerment program should be based on the needs of the main actors.